Case report: Minimal change disease and acute interstitial nephritis in a patient with Hodgkin's lymphoma treated with nivolumab. Issue 3 (October 2020) - Chemaly, Elie R; Sandoval Sus, Jose; Hussain, Faizul; Mogollon-Duffo, Francis; Laber, Damian A; Durr, Jacques A; Khalighi, Mazdak A; Lopez del Valle, Ramon
Programmed cell death receptor-1 blocking antibodies and cytotoxic T-lymphocyte–associated antigen-4 blocking antibodies are referred to as checkpoint inhibitors and are used in cancer immunotherapy. While enhancing T-cell antitumor immunity, checkpoint inhibitors can also cause immune-mediated nephrotoxicities, manifesting mostly in acute kidney injury. Cytotoxic T-lymphocyte–associated antigen-4 blockade was associated with acute interstitial nephritis with variable degrees of podocyte effacement, minimal change disease, and membranous nephropathy. Conversely, programmed cell death receptor-1 blockade has mostly been associated with acute interstitial nephritis, with or without various glomerular diseases. In particular, cases of minimal change disease were reported with programmed cell death receptor-1 blockade, including two cases of minimal change disease reported in Hodgkin's lymphoma and one with mesothelioma, in addition to one case of focal segmental glomerulosclerosis after treatment of renal cell carcinoma. We report a case of acute interstitial nephritis and minimal change disease in a patient with Hodgkin's lymphoma treated with nivolumab and discuss pathophysiological hypotheses. The association of minimal change disease with Hodgkin's lymphoma is well-recognized and may be related to c-mip protein and/or CD80. The checkpoint pathway likely triggers the auto-immune, T-cell-mediated, minimal change disease associated with Hodgkin's lymphoma; however, this pathogenic process may also involve a programmed cell death receptor-1– fyn-c-mip interaction or a PD-L1–CD80 cross-talk at both T-cell and podocyte level.